2019
DOI: 10.1111/flan.12412
|View full text |Cite
|
Sign up to set email alerts
|

Managing cognitive load with a flipped language class: An ethnographic study of the student experience

Abstract: This ethnographic study of a beginning‐level German course at an Australian university examined the student experience of learning second language (L2) grammar in a flipped classroom. Students accessed explicit grammar instruction and completed grammar exercises prior to attending face‐to‐face classes; during class, the structures were briefly reviewed by the students and then applied in interactive task‐based activities focused on meaningful use of the L2. In surveys and interviews, learners reported that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…By way of example, the flipped classroom effectively proved not only to produce deeper information processing but also to promote higher-order, in-depth thinking in the content-based second language through the asynchronous and synchronous learning stages. This conclusion matches the results obtained in the research performed by Tonkin, Page, and Forsey (2019): students experienced in the pre-class stage can reduce the intrinsic load during the in-class stage because having completed the pre-class activities endows them with sufficient prior knowledge to carry out in-class learning tasks with greater ease. Moreover, prior knowledge not only permits to reduce students' cognitive load during the in-class learning activity but also improves their performance.…”
Section: Discussionsupporting
confidence: 90%
“…By way of example, the flipped classroom effectively proved not only to produce deeper information processing but also to promote higher-order, in-depth thinking in the content-based second language through the asynchronous and synchronous learning stages. This conclusion matches the results obtained in the research performed by Tonkin, Page, and Forsey (2019): students experienced in the pre-class stage can reduce the intrinsic load during the in-class stage because having completed the pre-class activities endows them with sufficient prior knowledge to carry out in-class learning tasks with greater ease. Moreover, prior knowledge not only permits to reduce students' cognitive load during the in-class learning activity but also improves their performance.…”
Section: Discussionsupporting
confidence: 90%
“…The results validate Gelan et al (2018)'s research results that technology leads to a variety of affordances, and students feel more interested in participating in interactive activities after flipping. Besides, with the available affordances in flipped learning, students may have a better acquisition of receptive language knowledge, thus feeling more confident and competent to participate in various activities (Tonkin et al, 2019). Similar to Lee and Wallace (2018) work, the present study showed that students were more engaged in the learning process, with increasing attention paid to grammatical mistakes and linguistic errors (Chang & Lin, 2019) in the pre‐class discussion boards and in‐class interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The peer-assessment design in MosoTeach empowered students greatly (Bicen & Beheshti, 2022), and let them feel the ownership of their own learning (Shyr & Chen, 2018). This sense of empowerment and ownership also contrib- knowledge, thus feeling more confident and competent to participate in various activities (Tonkin et al, 2019). Similar to Lee and Wallace (2018) work, the present study showed that students were more engaged in the learning process, with increasing attention paid to grammatical mistakes and linguistic errors (Chang & Lin, 2019) in the pre-class discussion boards and in-class interactions.…”
Section: Students' Perceived Motivation Participation and Feedbackmentioning
confidence: 99%
“…Afterwards, when the main learning task begins, they are able to draw upon the content of the pre-task activity from their long-term memory, freeing up short-term memory processing for the task at hand. For language learners, pre-task activities can help improve confidence and make content easier to learn because of the reduction in cognitive load (Tonkin et al, 2019).…”
Section: Pre-task Activitiesmentioning
confidence: 99%